Could internal limiting membrane peeling before Voretigen neparvovec-ryzl subretinal injection prevent focal chorioretinal atrophy? - Lea Dormegny; Fouzia Studer; Arnaud Sauer; Laurent Ballonzoli; Claude Speeg-Schatz; Tristan Bourcier; Helene Dollfus; David Gaucher (Heliyon, 2024)
Purpose: To report the effect of internal limiting membrane (ILM) peeling prior to Voretigen Neparvovec-ryzl (VN) subretinal injection on focal chorioretinal atrophy development in patients presenting with RPE65-mediated Leber congenital amaurosis (LCA). Design: Retrospective case series. Methods: Three patients who underwent bilateral subretinal VN injection for RPE65-mediated LCA were followed up for 18–24 months. ILM peeling was performed unilaterally in patients 1 and 2 and bilaterally in patient 3. Chorioretinal atrophy was identified on fundus biomicroscopy, non-mydriatic retinography and/or ultrawide field fundus imaging. Best corrected visual acuity (BCVA), spectral-domain optical coherence tomography (SD-OCT), visual fields, full-field stimulus threshold (FST) and visual functioning questionnaire score (NEI-VFQ-25) were reported. Outcome measures were changes in BCVA, visual fields, FST, NEI-VFQ-25, and chorioretinal atrophy location. Results: Chorioretinal atrophy at the injection site exclusively developed in eyes which did not undergo prior ILM peeling. In patient 3, bilateral pre-operative nummular chorioretinal alterations progressed toward epithelial atrophic patches in the mid and extreme retinal periphery 18 months after VN injection. BCVA and visual fields improved bilaterally. NEI_VFQ 25 remained stable in patient 1 and improved in patient 2 and 3. FST test improved bilaterally in patient 3. Conclusions: ILM peeling prior to VN injection seems to be a smoother and safer technique to administer VN treatment and may prevent secondary focal atrophy development at the injection site. However, another type of more extended chorioretinal atrophy might exist and could be related to LCA evolution or to incompletely understood adverse effect of VN product.